Two strawberry miR159 family members display developmental specific expression patterns in the fruit receptacle and cooperatively regulate Fa-GAMYB - Csukasi, Fabiana; Donaire, Livia; Casañal Seoane, Ana; Martínez-Priego, Llúcia; Botella-Mesa, Miguel Ángel; Medina-Escobar, Nieves; Llave, César; Valpuesta-Fernández, Victoriano (Wiley, 2012)
We have reported previously that the gibberellin (GA) content in strawberry receptacle is high, peaking at specific stages, pointing to a role of this hormone in fruit development. In Arabidopsis, miR159 levels are dependent on GA concentration. This prompted us to investigate the role of two members of the miR159 family and their putative strawberry target gene, GAMYB, in relation to changes in GA content during the course of fruit development.
Keywords: Fresas; strwaberry; miR159; GAMYB; gibberellins; fruit